2001
DOI: 10.1021/om0009637
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of Functional Aryl- and Heteroarylchlorosilanes. Application to the Preparation of Donor−Acceptor or Donor−Donor Organosilicon Molecules

Abstract: A variety of functional aryl-and heteroarylchlorosilanes were prepared by electrochemical reduction of halothiophenes, halofurans, halopyridines, and substituted aryl halides in the presence of a large excess of commercial organodi-or trichlorosilanes using an undivided cell, a sacrificial Mg or Al anode, a constant current density, and tetrabutylammonium bromide as the supporting electrolyte. New structures are described, and some examples of the use of these more elaborate chlorosilanes are given, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…765 As another application of nickel catalyzed electroreductive transformations of aryl halides, silylation of aryl bromides was reported. 766 …”
Section: Cathodic Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…765 As another application of nickel catalyzed electroreductive transformations of aryl halides, silylation of aryl bromides was reported. 766 …”
Section: Cathodic Reductionmentioning
confidence: 99%
“…765 As another application of nickel catalyzed electroreductive transformations of aryl halides, silylation of aryl bromides was reported. 766 Complexes of cobalt and pyridine exhibit similar reactivity with nickel in that they readily undergo cathodic reduction to generate low valent Co species which are capable of oxidative insertion into aryl C−X bonds. The resulting organocobalt complex can undergo transmetalation with zinc salts, offering an efficient means to prepare organozinc reagents (Figure 44G).…”
Section: Cathodic Generation Of Low Valent Nickel and Cobalt Species:...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ramification is that even though the SiCl bond is reduced first, electroreduction of C‐Cl bonds to carbanions (eq 4 and 5, Scheme ) would be dominant. Another possible cause of preferential activation of CCl bonds involves the Ni(0)/TDA‐1 catalysis 30…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] They found that a large excess of chlorosilane, a strongly coordinating co-solvent (mostly hexamethyl phosphoric triamide HMPA) and/or a Ni catalyst, had to be used in order to preserve one of the chloro substituents on silicon (cf. Scheme 3).…”
mentioning
confidence: 99%